2021
DOI: 10.1002/jcla.23684
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lymph node metastasis in oral tongue squamous cell carcinoma using the neutrophil‐to‐lymphocyte ratio and platelet‐to‐neutrophil ratio

Abstract: Background Lymph node metastasis in a variety of tumors is associated with systemic inflammatory markers. However, this association has not been reported in oral tongue squamous cell carcinoma (OTSCC). This study aimed to investigate how the preoperative neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐neutrophil ratio (PNR) in OTSCC patients correlated with the occurrence of OTSCC and lymph node metastasis. Methods The data of 73 patients with primary OTSCC who underwent surgical resection were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In patients with metastatic colorectal cancer and upper urinary tract cancer with a tumor diameter >3 cm, the platelet/lymphocyte ratio was found to be correlated with tumor location and prognosis (106,107). In patients with oral and lingual squamous cell carcinoma, the platelet-to-neutrophil ratio can predict lymph node metastasis (108). Further research is needed to understand the mechanism of RNA transfer between platelets and tumor cells; this would include the use of mouse models, megakaryocyte analysis, and platelet RNA and proteomic multi-omics analysis.…”
Section: Emerging Technologies For Tumoreducated Platelets Biomarkersmentioning
confidence: 99%
“…In patients with metastatic colorectal cancer and upper urinary tract cancer with a tumor diameter >3 cm, the platelet/lymphocyte ratio was found to be correlated with tumor location and prognosis (106,107). In patients with oral and lingual squamous cell carcinoma, the platelet-to-neutrophil ratio can predict lymph node metastasis (108). Further research is needed to understand the mechanism of RNA transfer between platelets and tumor cells; this would include the use of mouse models, megakaryocyte analysis, and platelet RNA and proteomic multi-omics analysis.…”
Section: Emerging Technologies For Tumoreducated Platelets Biomarkersmentioning
confidence: 99%
“…TSCC, as a tumor with an extremely high incidence in the oral and maxillofacial region, has a 5-year survival rate of less than 50%, although with the continuous improvement of surgery as well as comprehensive treatments such as radiotherapy and chemotherapy (Carr et al 2021). Among them, the significant biological predisposition to local invasion and the high incidence of early cervical lymph node metastasis are important factors contributing to the poor prognosis of patients with TSCC (Wang et al 2021a). In this study, we found that the invasion and migration abilities as well as EMT of TSCC cells were significantly enhanced under hypoxia.…”
Section: Discussionmentioning
confidence: 58%
“…When OSCC did not metastasize, innate immunity was dominant, and the neutrophil count was elevated; after tumor metastasis, innate immunity weakened, and adaptive immunity became dominant. The neutrophil count decreases significantly compared to before tumor metastasis, and the mean lymphocyte count is greater than that in the no-metastasis group, resulting in a low NLR in the OM group [23]. This study identified a lymphocyte count of 1518/mm 3 as the cut-off value in survival with ROC analysis; a significant difference in OM was identified between <1518/mm 3 vs. ≥1518/mm 3 .…”
Section: Discussionmentioning
confidence: 74%